Gender and Proximity Marketing : Concept, Antecedents, and Effects - Pattnaik, Pinaki Nandan; Hota, Sweta Leena; Shukla, Mahendra Kumar; Matloob, Afsha (Indian Journal of Marketing, 2025)
Purpose : This paper examined the concept of proximity marketing and its effectiveness by identifying its antecedents and evaluating the moderating role of gender. It specifically tried to explore how gender influenced the relationship between proximity marketing effectiveness and factors like customer orientation, quality, privacy, and perceived usefulness, thus attempting to provide a deeper understanding of how gender shapes consumer responses to proximity marketing initiatives. Design/Methodology/Approach : A cross-sectional descriptive research design was used. The primary data was collected through an online survey. The final sample size was 763. The measurement items were adapted from earlier studies (in a similar context) to operationalize the constructs included in this research using a 7-point Likert scale (1 = strongly disagree; 7 = strongly agree). Findings : The study found that perceived usefulness (PU) significantly enhanced proximity marketing effectiveness (PME), as did compatibility, with information quality (IQ) being a strong predictor of PME. Similarly, cognitive innovativeness positively correlated with the effectiveness of proximity marketing, while PU and customer orientation did not significantly influence cognitive innovativeness. IQ had a positive effect on cognitive innovativeness, and privacy and security concerns had a negative impact on customer innovativeness. Originality/Value : This is the first study (as per the authors’ knowledge) to use a large-scale empirical survey to examine the relationship between proximity marketing’s effectiveness and its antecedents.